Keputusan Perempuan Memaafkan Ketidaksetiaan Pasangan - Zulfa Safitri K; Amirudin Amirudin (Endogami: Jurnal Ilmiah Kajian Antropologi, 2021)
A Woman’s Decision To Forgive Partner’s Infidelity: Infidelity is a form of violence against a partner that has negative impact on physical and psychological health. For those who are loyal with only one partner, type of sexual or emotional infidelity has a strong effect on the relationship. Analysis from previous studies show that infidelity often reported as the cause of breakup. However, the author argue that it is not certain that infidelity end up with breakup, beause apart from internal factors, social cultural factors also need to be considered as the reason for decision making. The writing of this article aims to analyze women’s consideration in making decision to forgive and still stay with unfaithful partner. Methods and data analysis using previous literature studies regarding women’s decision making to forgive their partenr’s infidelity. Then it will be analyzed using concept of Gender Anthropology. The result show that culture is more tolerant or men who are not loyal than woman. In addition, woman have moral and material dependence on their partners. So, it can be concluded that the consideration of women to forgive and stay is due to domination and power relation.